If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -78 + -10x = 7x + 4 Reorder the terms: -78 + -10x = 4 + 7x Solving -78 + -10x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -78 + -10x + -7x = 4 + 7x + -7x Combine like terms: -10x + -7x = -17x -78 + -17x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 -78 + -17x = 4 + 0 -78 + -17x = 4 Add '78' to each side of the equation. -78 + 78 + -17x = 4 + 78 Combine like terms: -78 + 78 = 0 0 + -17x = 4 + 78 -17x = 4 + 78 Combine like terms: 4 + 78 = 82 -17x = 82 Divide each side by '-17'. x = -4.823529412 Simplifying x = -4.823529412
| h+5+4=10+10 | | 203-3x=42x-23 | | 12-9x=64-23x | | y=7x-2 | | 52-4x=5x+24 | | 16c=12+24c | | 3g-1=23 | | (x-12)+(16-2*x)=14 | | x*x+x+6=0 | | 2p+7q=46 | | 20yx=10-5yx | | 5y-11y= | | (x-12)+(16-2x)= | | 15yx=5-10yx | | -12(x-12)=-9(1+7) | | 5x+5=7+x | | 10x-17y= | | 13b=7-16b | | 3(w-2)=11 | | 2F=18 | | -16x=2-4x | | (4x+12)-8=(12+3x)-8 | | 9x+6y+2=0 | | 3(2q-7)-(3q-8)=22 | | 4x^2-27x+23=-4x+8 | | x+(x+4)=3+(x+1) | | 6x+14=23-3x | | 10x=51-7x | | -14x=7-9x | | x^2-9x-3=-8x-1 | | 3x+4=58-3x | | x^2+4x-28=4 |